THE INFLUENCES OF CUSTOMER RELATIONSHIP MANAGEMENT TO CUSTOMER SATISFACTION IN GAUDI CLOTHING STORE MANADO - Palapa, Georgiana Gloria (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The need is increasing and rapid technological development in the era of globalization, free markets, the increasingly fierce competition made the company create products to meet diverse consumer needs. The purpose of this study to analyze the influence of the value of the product, point of communication, loyalty programs, special services in the purchase of clothing at a boutique Gaudi both simultaneously and partially. Samples are determined based on the formula Slovin as many as 80 users. The method used is the Multiple regression, hypothesis testing using F & T test results showed simultaneous product value , contact point, loyalty programs, special services significantly influence the buyer's satisfaction. Partially product value, loyalty program, special service significantly influence the customer satisfaction while the contact point no significant effect on customer satisfaction. Gaudi management should create a new marketing strategy that is more spread acknowledgement about their product and strengthen their media that supported the communication with customer. Keyword : product value, contact point, loyalty program, special service